#### Question

In the following, find the value of *k* for which the given value is a solution of the given equation:

x^{2} + 3ax + k = 0, x = -a

#### Solution

We are given here that,

x^{2} + 3ax + k = 0, x = -a

Now, as we know that x = -a is a solution of the quadratic equation, hence it should satisfy the equation. Therefore substituting x = -a in the above equation gives us,

x^{2} + 3ax + k = 0

(-a)^{2} + 3a(-a) + k =0

a^{2} - 3a^{2} + k = 0

-2a^{2} + k = 0

k = 2a^{2}

Hence the value of k = 2a^{2}.

Is there an error in this question or solution?

#### APPEARS IN

Solution In the Following, Find the Value Of K For Which the Given Value is a Solution of the Given Equation: X2 + 3ax + K = 0, X = -a Concept: Quadratic Equations.